Popularitas Sanggar Tari Svarga Art Dance sebagai Organisasi Seni Pertunjukan Tari di Kabupaten Bungo - Nurhana Nurhana; Indrayuda Indrayuda (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to reveal and describe the popularity of the Svarga Art Dance Studio as a dance performance art organization in Bungo Regency. This type of research is qualitative research using a descriptive method. The instruments of this research are interviews, observations and documentation. The steps of analyzing data are data reduction, data presentation and data verification as well as conclusions. The results of the study show that the Svarga Art Dance Studio is very popular in Bungo Regency, this is evidenced by the achievements, as well as the many new dance creations that are only owned by the Svarga Art Dance Studio and become an attraction so as to increase the love of the people of Bungo Regency for dance arts. With the form of democratic management, the performance of the Svarga Art Dance Studio between branches 1 and 2 and its cooperation with UMMUBA UKM of the University of Muhammadiyah Bungo went well and was growing. This, supported by the marketing of the Svarga Art Dance dance studio which uses the Social Media Marketing system through the official Instagram and Tiktok accounts, is also supported by the personal branding owned by the owner of the studio, with this the Svarga Art Dance dance studio can achieve its popularity. The Svarga Art Dance Studio until now has many routines in its performance which are often used by agencies, governments and the general public both inside and outside Bungo Regency.